Pengaruh Good Corporate Governance (GCG), Investment Opportunity Set (IOS) dan Risiko Keuangan Terhadap Nilai Perusahaan - Warisqia Dwi Yuli Lestari; Tumirin Tumirin (Jurnal Riset Ekonomi dan Akuntansi, 2024)
This research aims to examine Good Corporate governance, Investment Opportunity Set and Financial Risk on Company Value. The population used is manufacturing companies that have been listed in the Indonesia Stock Exchange (BEI) for 1 period in 2022. The sample was selected using a purposive sampling technique of 100 samples. This research uses quantitative methods and secondary data sources from annual financial reports. This research results that Good Corporate Governance which includes independent commissioners, institutional ownership, managerial ownership has no effect on company value, Investment Opportunity Set has a significant positive effect on company value, and financial risk has a significant negative effect on company value.